NMOS Linear Image Sensors: A Review of Data Acquisition and Monitoring - Manoj, Abhishek; A, Akshay; Jamal, Jiya; S, Reshmi (International Journal of Computer Sciences and Engineering, 2024)
This paper analyzes data acquisition and monitoring techniques used with negative-metal-oxide semiconductor (NMOS) linear image sensors. NMOS sensors have gained significant attention in various fields due to their advantages in terms of sensitivity, dynamic range, and low noise characteristics. Through a systematic review, the paper explores the fundamental characteristics of NMOS sensors, including their operation, sensitivity, and limitations. Data acquisition techniques will cover readout circuits, sensor resolution, timing characteristics and monitoring stratergies. A microcontroller can receive the gathered data and store it for later use